Performance study of a new epoxy resin IR-3 in HTS-based high-field magnet application. (1st June 2022) - Yao, Huanli; Zhang, Zhen; Wang, Chengtao; Wang, Yingzhe; Feng, Ze; Shi, Jinrui; Zhao, Yalin; Zhang, Hua; Li, Chunyan; Kang, Rui; Liu, Fang; Liu, Huajun; et al.
Abstract: REBCO (Rare-earth-based barium copper oxide) conductors are appropriate materials for high-field magnet applications. Vacuum impregnation using epoxy resin is a technique widely used for stable operation of superconducting coils. However, epoxy-impregnated REBCO coils often experience critical current degradation problems. Finding a suitable impregnating material for REBCO coils is important for their application in high-field superconducting magnets. A new toughness epoxy, IR-3, was developed recently. An in-depth understanding of IR-3 on the performance of REBCO coils is critically necessary for its application. Thus, this paper explores the effects of IR-3 impregnation on the performance of REBCO coils at 77 K and 4.2 K. The test results are compared to similar coils impregnated with CTD-101 K and MY750. Meanwhile, the radial stresses at 77 K in self-field and 4.2 K under 10 T were simulated. All epoxy impregnated REBCO coils showed no decay in critical current after thermal cycles at 77 K. When charged at 4.2 K in external fields of 5 T and 10 T, the IR-3 impregnated REBCO coils avoided performance degradation problems and had superior electrical stabilities. Combing the excellent performance at low temperatures, IR-3 is a promising candidate material for impregnating high-field REBCO coils.